Erosion, corrosion and erosion-corrosion of EB PVD thermal barrier coatings - Wellman, R. G.; Nicholls, John R. (Elsevier Science B.V., Amsterdam., 2008)
Electron beam (EB) physical vapour deposited (PVD) thermal barrier coatings (TBCs) have been used in gas turbine engines for a number of years. The primary mode of failure is attributed to oxidation of the bond coat and growth of the thermally grown oxide (TGO), the alumina scale that forms on the bond coat and to which the ceramic top coat adheres. Once the TGO reaches a critical thickness, the TBC tends to spall and expose the underlying substrate to the hot gases. Erosion is commonly accepted as a secondary failure mechanism, which thins the TBC thus reducing its insulation capability and increasing the TGO growth rate. In severe conditions, erosion can completely remove the TBC over time, again resulting in the exposure of the substrate, typically Ni-based superalloys. Since engine efficiency is related to turbine entry temperature (TET), there is a constant driving force to increase this temperature. With this drive for higher TETs comes corrosion problems for the yttria stabilised zirconia (YSZ) ceramic topcoat. YSZ is susceptible to attack from molten calciumÃ¢Â Â magnesiumÃ¢Â Â aluminaÃ¢Â Â silicates (CMAS) which degrades the YSZ both chemically and micro-structurally. CMAS has a melting point of around 1240 Ã Â°C and since it is common in atmospheric dust it is easily deposited onto gas turbine blades. If the CMAS then melts and penetrates into the ceramic, the life of the TBC can be significantly reduced. This paper discusses the various failure mechanisms associated with the erosion, corrosion and erosionÃ¢Â Â corrosion of EB PVD TBCs. The concept of a dimensionless ratio D/d, where D is the contact footprint diameter and d is the column diameter, as a means of determining the erosion mechanism is introduced and discussed for EB